The effect of rubber mats on lesions and lameness in gilts housed in gestation stalls - Ostović, Mario (Array, 2020)
Rubber mats have not yet been widely established in pig production. However, studies mostly focusing on lesions, lameness and behaviours of lactating and group-housed pregnant sows have reported favourable results. To the best of our knowledge, lesions and lameness in sows or gilts housed individually in rubber floor gestation stalls have not been previously investigated. This study was carried out on a commercial pigbreeding farm service unit during a 28-day production cycle in all seasons. Twentyeight gilts were divided into two equal groups, control and experimental groups, and observed for each cycle. The control group was housed in standard gestation stalls with concrete slatted floor, which in the experimental group was covered with an adjusted rubber mat. During each cycle, lesions were scored on days 1, 8, 15 and 28, and lameness on day 1 and upon gilt transfer from the service unit on day 29. Gilts in rubber floor stalls showed significant reduction (P<0.05) in lesions during the cooler period. Conversely, mats had no impact on lameness score in any season. No significant correlations were found between lesions and the percentage of gilts with a particular lameness score. Accordingly, rubber flooring may improve the welfare of gilts in gestation stalls through lower lesion incidence; however, ambient temperature should be taken into consideration when available.